Study the effect of attenuation and analysis of wireless LAN signal in an indoor environment with some physical obstacles - Hasan, Hasan J (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Wireless communication technology using local area network (LAN)technology is considered the most widely used communication technology today, especially in indoor places such as companies, hospitals and homes . But there are downsides that affect the work of this technology, especially the interference that occurs with these waves and the impact of some physical obstacles, and these two characteristics are considered one of the most prominent challenges facing the spread of this technology.. These waves are affected by numerous physical obstacles along their propagation path, such as building walls and iron or wood sections, which sometimes obstruct the waves. This study highlights a practical study of the effect of the thickness, proximity, and distance of these obstacles on the signal source. A 2.4 GHz router was used. It was observed that the thickness of some obstacles has a significant impact on the quality of the transmitted signal, as does the distance of the signal source from the user. Based on the results extracted from this practical study, a set of points emerge that must be taken into account to improve the quality of transmission and reception of such waves.